Pneumatic system for pressure probe measurements in transient flows of non-ideal vapors subject to line condensation. (31st March 2022) - Conti, Camilla C.; Fusetti, Alberto; Spinelli, Andrea; Gaetani, Paolo; Guardone, Alberto
Abstract: This paper presents the design, construction and commissioning of a pneumatic system for pressure probe measurements in flows of organic vapors in non-ideal conditions, namely in the thermodynamic region close to the liquid–vapor saturation curve and the critical point where the ideal gas law is not applicable. Experiments were carried out with fluid siloxane MM (hexamethyldisiloxane, C 6 H18 OSi 2 ), commonly employed in medium/high temperature Organic Rankine Cycles (ORCs), in the Test Rig for Organic VApors (TROVA), a blow-down wind tunnel at the Laboratory of Compressible fluid dynamics for Renewable Energy Applications (CREA lab) of Politecnico di Milano. TROVA operation is intrinsically transient due to its batch nature, with a low frequency content ( ∼ 1 Hz ) related to the emptying of the high-pressure reservoir feeding the test section. The challenges linked to possible condensation in pneumatic lines, such as vapor–liquid menisci, hydrostatic head and mass-sink effects, were evaluated by means of theoretical calculation and experiments. To avoid these issues, a nitrogen-flushed pneumatic system for absolute and differential pressure measurements was designed and successfully tested with superheated MM vapor expanding in planar choked converging nozzles characterized by a portion with constant cross-sectional area yielding design Mach numbers of 0.2, 0.5 and 0.7. Commissioning of the complete system including a probe was performed with the first ever testing of an L-shaped Pitot tube in non-ideal subsonic flows of siloxane MM vapor at Mach numbers M = 0 . 2 and 0.5. Measurement delay issues were identified and assessed through a dynamic testing procedure, and were solved by reducing the overall pneumatic lines volume including the one hidden within pressure transducers. The correct performance of the complete system was therefore verified for probe measurements of total, static and dynamic pressure in non-ideal flows of organic vapors. This sets the foundation for future directional pressure probes calibration and use in the characterization of such flows, as in direct measurement of total pressure losses across shocks and in testing of ORC turbine blade cascades. Graphical abstract: Highlights: Step-by-step development of a pneumatic system for pressure probe measurements. Non-ideal flows of organic vapor in conditions typical of Organic Rankine cycles. Nitrogen-flushing system to prevent line condensation. Avoided vapor–liquid menisci, hydrostatic head and response delay due to mass sink. Dynamic testing for response time and overall line volume minimization.